Композиційні прийоми новели у поетиці кіносценарію (“Перевірте свої годинники” Ліни Костенко та Аркадія Добровольського) - Нікоряк, Наталія (Чернівці : Буковинський державний медичний університет, 2022)
The article is aimed to analyze the specifics of the compositional organization of the film script “Check Your Watches” (1962) by L. Kostenko and A. Dobrovolskiy, which is based on the genre matrix of the novella. Research methods comprise intermedial, genre study, stylistic and receptive analyses. The relevance of the study: the paper actualizes the issue of genre continuity between literature and cinema in the aspect of poetics on the example of a screen-play text. Conclusion: Since among all the prose genres of short prose, the novella is particularly intense in plot and reduced eventfulness, conciseness, clear depicting of characters, semantic capacity, it brings it closer to the film dramatic narrative. As a result, there is an increased attention of filmmakers to this genre, using it not only in the development of episodes or in creating a special type of feature film (for example, consisting of a chain of novellas), but also as a compositional technique of scriptwrit-ing. Taken as an example, the film script by Lina Kostenko and Arkadiy Dobrovolskiy “Check your watches” clearly demon-strates the practical use of the novella genre model at the levels of plot, composition, personosphere, etc. Screenplay integrity of composition, dynamism, conciseness, and completeness of the individual episodes create a generalized tone and certain monu-mentality to the work. Even though the form of the film novel is “deprived” of the possibility of giving a multiplanar image of life, however, the authors manage to recreate multiplanarity, a passionate horizon of expectation. Like none other, Lina Kostenko knew from inside all the problems and torments of creativity; subtly feeling the poet`s soul, she managed to fulfill the stories of the “young poets” with life.
COMPOSITIONAL TECHNIQUES OF THE NOVELLA IN THE POETICS OF THE FILM SCRIPT (“CHECK YOUR WATCHES” BY LINA KOSTENKO AND ARKADIY DOBROVOLSKIY)
Keywords: novella; film script; genre matrix; composition; editing; “Check your watches”; L. Kostenko; A. Dobrovolskiy